UPAYA PENDIDIK PAI DALAM MEMBINA KUALITAS AKHLAK SISWA/SISWI SEKOLAH MENENGAH PERTAMA ISLAM MA’ARIF 2 MALANG - Achmad Eka Febrianto; Azhar Haq; Lia Nur Atiqoh Bela Dina (VICRATINA, 2019)
The Glory and the height of a teacher given by Allah SWT is that he can teach knowledge to others, and in general Islamic Education teachers are educators who teach Islamic educational norms sourced from the Qur'an and Hadith of Morals are a reflection from someone who can be judged by others through their behavior and personality, because it is the morality that will become the forerunner of the formation of character or human nature and must be instilled early on in someoneKeywords: Pendidik, Membina, Kualitas Akhlak